Institutional contexts, institutional capability and accelerated internationalization of entrepreneurial firms from emerging economies. Issue 2 (5th June 2017) - Huang, Sheng; Ye, Guangyu; Zhou, Jinbo; Jin, Tiantian
Abstract : Purpose: This paper aims to reveal the influencing mechanism of the interaction between institutional environments in the home and host country on the accelerated internationalization of entrepreneurial enterprises from emerging economies (EE). The authors want to open the black box of home-country institutional environments' moderating mechanism on the relationship between host-country institutional environments and accelerated internationalization. Design/methodology/approach: The authors chose a massive interview method and case study method to answer this question. According to our standards, the authors chose four high-tech companies in Guangdong and Guangxi provinces as case study samples. During investigation in the four case companies, the authors collected print data of 150 pages and electric data of 3 pages. Then, the authors excavated concepts in data through open coding, axial coding and select-type coding and identified concepts' dimensions and connections between them. Findings: Well-developed home-country institutions can reduce the inhibitory effect of under-developed host-country institutions on the accelerated internationalization of entrepreneurial enterprises from emerging economies. Under-developed institutional environments in the home country are beneficial for entrepreneurial enterprises from EE to develop the institutional capability for entrepreneurial enterprises with stronger institutional capability from emerging economies. The inhibitory effect of under-developed institutional environments in the host country on their accelerated internationalization is weaker. The positive moderating role played by institutional voids in the home country on the relationship between institutional voids in the host country and the accelerated internationalization are mediated by the institutional capability of entrepreneurial enterprises from emerging economies. Research limitations/implications: The authors just refined the definition of institutional capability and divided its dimensions. Issues such as operationalization of institutional capability and the development of measurement scale are also worthy for future quantitative research. Considering the inherent defect of case study and that these four case companies are from Chinese high-tech industry, the external validity our research may be limited. The theoretical model that was constructed generally captured the relationships between dual institutional environments, institutional capability and EE entrepreneurial firms' accelerated internationalization decision. Future studies may use a large-scale sample to verify the all propositions the authors introduced to draw more steady and reliable empirical study results. Practical implications: The conclusions have significant implications for governments in EE to construct friendly institutional environments for international entrepreneurship and for entrepreneurial firms to implement internationalization strategies. Social implications: Policy makers should establish well-developed normative and cognitive institutional environment by cultivating global-orientated and open national culture and organizing experience exchange conference, thereby speeding up the implementation of internationalization strategies and further improving international competitiveness for a country. Originality/value: First, the authors defined institutional capability as firms' ability of establishing relationships with institution actors, adapting to institutional contexts, changing existing institutions or creating new ones to gain potential interests and suggested that it consists of three dimensions. Second, institutional voids in the home country positively moderate the relationship between under-developed institutional environments in the host country and the accelerated internationalization of entrepreneurial firms from EE. At last, institutional capability of firms negatively moderates the relationship between under-developed institutional environments in the host country and the accelerated internationalization of entrepreneurial firms from EE.